The Effect of eWOM as Mediation of Website Quality and Trust - E Dita Septiari (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2018)
The purpose of this paper is to examine consumer attitudes toward online shopping in Marketplace, Shoppee. The paper used three variables which includes trust, perceived website quality, and electronic word of mouth (eWOM) along with their relationships in order to examine the effects of eWOM as mediator toward website quality and trust relationship. An offline survey was employed targeting online shoppers of Shoppee, one of reputable marketplace in Indonesia. A sample of 200 students in Universitas Atma Jaya Yogyakarta as online shoppers was involved in the online survey. Regression and Path analysis was used to test the hypothesized relationships of the research model. The empirical findings of this research shows that website quality and eWOM are predictor of consumer trust. Hence, EWOM also has mediation effect. The implication of this research is to support the importance of eWOM as key drivers to build trust among customers in online shopping. It also underlines the importance of website quality as important factors in online shopping.Keywords: eWOM, Website quality, Trust, Online Shopping